Grundtvigs anvendelse af modsigelsen grundsætning i "Kirkens Gienmæle" - filosofisk belyst - Kelstrup, Erik (Grundtvig-studier, 2000)
The principle of contradiction in Kirkens Gienmæle« - in a philosophical light By Erik Kelstrup The article has two purposes. The first one is to show some characteristic ways, in which the principle of contradiction has been understood in the history of philosophy. This philosophical overview should serve as a basis for analysing Grundtvig’s use of the principle of contradiction.The second purpose, is in connection to this, to analyse Grundtvig’s use of the principle in the important pamphlet » Kirkens Gienmæle« (1825). The view presented here is that H. Høirup’s claim that the principle is a theological axiom for » Kirkens Gienmæle«, is if not entirely wrong, then at least exaggerated.The first part of the article begins with a presentation and discussion of Aristotle’s understanding of the principle of contradiction. It is shown that Aristotle understands the principle as a primary ontological principle, but that in his argumentation for the principle he actually argues in linguistic ways. Consequently there is a tension between an ontological and a linguistic way of understanding the principle of contradiction in Aristotle. The ontological claim of the principle continues in the philosophy of Christian von Wolff, from whom Grundtvig received his way of understanding the principle through his teacher in propadeutic philosophy, Børge Riisbrigh. Against Wolff Immanuel Kant argues that the principle of contradiction can only be used as an entirely formal and negative principle of truth. It has no connection to reality. The rejection of the ontological relevance of the principle continues in the analytical philosophy nowadays. So E. Tugendhat and P. F. Strawson argue that the principle of contradiction expresses only a necessary condition, if speech is to be meaningful. To speak in contradictions, is to say nothing. Such a speech does not have to be pointless, but if it is not explained, there will be given no information. In a critical reflection on the Aristotelian understanding of the principle of contradiction Tugendhat also emphasizes (in agreement with Strawson), that the predicative expression, which is contradicted in a contradiction, can only be understood on the basis of the situation in which it is used. This leads him to a corrected formulation of the Aristotelian principle of contradiction. Tugendhat’s formulation implies, however, that the principle is only an interior linguistic matter. It does not say anything about how the connection between language and reality should be. Therefore contradictions are not to be understood as false statements (against Kant). As Strawson puts it: there is a difference between declaring that a man’s remarks are untrue, and declaring that they are inconsistent. In the first case the relation to reality is the central issue, in the second it is not.In the second part of the article » Kirkens Gienmæle« is closely analysed with regard to the principle of contradiction. Here it is argued that although Grundtvig seems to find it useful to criticize H. N. Clausen for contradicting himself, and although he declares that Clausen’s contradictions are indications that Clausen is lying, the real argumentation takes place in a comparison between Grundtvig’s and Clausen’s understandings of church and Christianity. This means that the theological axiom is first and foremost Grundtvig’s view of the church, the socalled »kirkelige anskuelse«. Grundtvig’s opinion (in agreement with Kant) that contradiction and falseness are closely related, is rejected on the basis of Strawsons argumentation. But this opinion plays a minor role in » Kirkens Gienmæle«. It is also argued that Grundtvig’s examples of inconsistent thoughts in Clausen’s theology are purely linguistic (as Strawson and Tugendhat would accept it). The principle of contradiction is not used ontologically (as it is in Aristotle and Wolff). Therefore Grundtvig’s attack on Clausen is not epistemological (in opposition to Høirup). Grundtvig is not defending Wolff against Kant. Furthermore it is argued, that Grundtvig’s use of the principle of contradiction is totally superfluous. The actual argumentation is grounded in the demonstration, that Clausen’s understanding of the church is untrue, because it stands in opposition to (what Grundtvig thinks is) the true understanding of the church. And this demonstration and argumentation does not depend on the principle of contradiction. Finally the principle is not at all used (positive or negative) in defining the ground on which the whole pamphlet depends: the true view of the church.